TUJUH KONSEP DA’WAH BIL-HIKMAH MENURUT MOHAMMAD NATSIR - Ahmad Misbahul Anam (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2020)
Da'wah in this country began long before Indonesia reach independence. Transformation of society has been heavily influenced by Islam through people who give or extend rightenousness or called da’I from the past until now. The tough da'wah defiance be easier by offering of procedures to convey Islamic messages. Mohammad Natsir, one of the da'wah leaders and statesmen offered seven concepts of da'wah bil-hikmah as the procedures for da'wah. His ideas about the concept of da'wah bil-hikmah was written in his book with title “Fiqh Da'wah”. This research tries to study indepth his idea by analyzing the text in the book. The conclusion of this study, Natsir has good concepts that useful for da’I to convey rightenouness of da'wah. It is indicated by showing and explaining about the guidance of ayats in Al Qur’an, stories of prophets and their follower that associated with strong local wisdem, and it becomes his characteristic.